Words in time a plea for historical re-thinking - Benigno, Francesco 1955- (Routledge, Taylor & Francis Group, 2017)
"Examines the origins and development of the words we use, critiquing the ways in which they have traditionally been employed in historical thinking and examining their potential usefulness today"...Provided by the publisher
Includes bibliographical references and index
Keywords: Sozialwissenschaften; Historiography; Social sciences -- Historiography; Terminologie; Sprachanalyse; Geschichtswissenschaft